2014
DOI: 10.3402/gha.v7.24089
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study on attitudes toward gender equality, sexual behavior, positive sexual experiences, and communication about sex among sexually active and non-sexually active adolescents in Bolivia and Ecuador

Abstract: BackgroundIt is widely agreed upon that gender is a key aspect of sexuality however, questions remain on how gender exactly influences adolescents’ sexual health.ObjectiveThe aim of this research was to study correlations between gender equality attitudes and sexual behavior, sexual experiences and communication about sex among sexually active and non-sexually active adolescents in 2 Latin American countries.DesignIn 2011, a cross-sectional study was carried out among 5,913 adolescents aged 14–18 in 20 seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 42 publications
4
43
1
6
Order By: Relevance
“…9 Another cross-sectional study of 5913 adolescents aged 14-18 years in 20 secondary schools in Bolivia and six secondary schools in Ecuador showed that sexually active adolescents who consider gender equality important report higher use of contraceptives, are more likely to describe their last sexual intercourse as a positive experience and consider it easier to talk with their partner about sexuality compared with sexually experienced adolescents who are less positively inclined towards gender equality. 3 These correlations were consistent for boys and girls. Non-sexually active adolescent boys and girls who consider gender equality to be important are also more likely to: (i) think that sexual intercourse is a positive experience; (ii) consider it less necessary to have sexual intercourse to maintain a relationship; and (iii) find it easier to communicate with their girlfriend/ boyfriend compared with sexually non-active adolescents who consider gender equality less important.…”
Section: 2supporting
confidence: 61%
See 3 more Smart Citations
“…9 Another cross-sectional study of 5913 adolescents aged 14-18 years in 20 secondary schools in Bolivia and six secondary schools in Ecuador showed that sexually active adolescents who consider gender equality important report higher use of contraceptives, are more likely to describe their last sexual intercourse as a positive experience and consider it easier to talk with their partner about sexuality compared with sexually experienced adolescents who are less positively inclined towards gender equality. 3 These correlations were consistent for boys and girls. Non-sexually active adolescent boys and girls who consider gender equality to be important are also more likely to: (i) think that sexual intercourse is a positive experience; (ii) consider it less necessary to have sexual intercourse to maintain a relationship; and (iii) find it easier to communicate with their girlfriend/ boyfriend compared with sexually non-active adolescents who consider gender equality less important.…”
Section: 2supporting
confidence: 61%
“…Non-sexually active adolescent boys and girls who consider gender equality to be important are also more likely to: (i) think that sexual intercourse is a positive experience; (ii) consider it less necessary to have sexual intercourse to maintain a relationship; and (iii) find it easier to communicate with their girlfriend/ boyfriend compared with sexually non-active adolescents who consider gender equality less important. 3 Furthermore, findings from 10 studies in Latin America, Asia and Africa found significant associations between support for inequitable gender norms and increased risk of partner violence and unprotected sex. 6,7 Qualitative research suggests that pervasive norms about how males and females are supposed to behave can affect sexual risk behaviours; for example, young women may be unwilling to carry condoms or request their use because of the implication that they are sexually promiscuous.…”
Section: 2mentioning
confidence: 99%
See 2 more Smart Citations
“…Hasil penelitian ini menunjukkan bahwa ada hubungan relasi gender dengan perilaku seksual aman pada remaja putri di Kabupaten Karanganyar. Hasil penelitian ini sejalan dengan penelitian Meyer et al, (2014) bahwa pasangan remaja yang menganggap bahwa kesetaraan gender merupakan hal penting dalam hubungan berpacaran mempunyai angka penggunaan kontrasepsi lebih tinggi. Kesetaraan gender dalam berpacaran mempunyai dampak yang posi-tif terhadap kesehatan reproduksi pada remaja.…”
Section: Hubungan Persepsi Kontrol Perilaku Dengan Perilaku Seksual Aunclassified